2009
DOI: 10.1007/s00198-009-0930-1
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to monthly and weekly oral bisphosphonates in women with osteoporosis

Abstract: Summary This primary care database survey evaluated whether osteoporotic women treated with bisphosphonates were more adherent to monthly than to weekly treatment. Both compliance (medication possession ratio [MPR]) and persistence (time to discontinuation) were superior in the monthly ibandronate treatment group. Better control of fracture risk may thus be achieved using monthly treatment regimens. Introduction Treatment adherence in osteoporosis is poor. The objective of this study was to evaluate whether mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
3
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 45 publications
(47 reference statements)
4
78
3
6
Order By: Relevance
“…This is probably related to complicated dosing instructions and poor gastrointestinal tolerability which certainly have an impact on QoL. Several studies reported improved adherence with reducing bisphosphonate dosing frequency (12,13). Moreover, data has shown that less frequent dosing is more convenient for the patient (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…This is probably related to complicated dosing instructions and poor gastrointestinal tolerability which certainly have an impact on QoL. Several studies reported improved adherence with reducing bisphosphonate dosing frequency (12,13). Moreover, data has shown that less frequent dosing is more convenient for the patient (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Select the First Affiliated Hospital of Wenshan City orthopedic surgery in March 2013-2014 in November accommodated 220 cases of glucocorticoid hormones of patients with osteoporosis were randomly divided into treatment and the principle of distribution control group, 110 cases, the treatment group in 110 cases, 58 males and 52 females, aged 27 to 49 years, mean (33.3 ± 2.3) years; the control group 110 cases, 67 males and 43 females, aged 24 to 53 years, mean (36.7 ± 2.5 )year old.Inclusion and exclusion criteria [4][5] Year of continuous treatment, regular follow-up and in the course of treatment, bone mineral density was observed before and after treatment in patients with bone mineral density in two groups of patients in particular L1~L4 lumbar spine and femoral neck bone. Disable other medications affecting bone metabolism of drugs such as anti-epileptic drugs and anticoagulants.Determination of bone mineral density [6] : After treatment, all subjects with BMD digital dual energy X-ray bone density measuring instrument measurement, patients were measured and L1~L4 lumbar spine and femoral neck bone mineral density, the instrument accuracy 1% repeat error <1% to BMD bone mineral density (g/cm 2 ) is displayed.…”
Section: General Information Actmentioning
confidence: 99%
“…A high strength of evidence shows that weekly dosing is associated with higher adherence than daily dosing regimens; 23,31,[34][35][36][37][38][39][40][41][42][43][44] but there is insufficient evidence that monthly regimens are associated with higher adherence compared with weekly regiments. 28,29,33,[45][46][47] Adverse effects and concerns about adverse effects are important predictors of adherence and persistence. A systematic review and data from 15 of 17 observational studies provide a moderate strength of evidence that adverse effects from bisphosphonates are associated with decreased adherence and increased risk of fracture (vertebral or nonvertebral or both).…”
Section: ■■ Variance Of Short-and Long-term Adverse Effects Of Therapmentioning
confidence: 99%